The Influence of TikTok Fashion Trends on Students' College Outfit Choices - Agung Rorhi Prayudha; Putri Delvina Sari; Fitriana Fitriana (Universitas Negeri Semarang, 2024)
This study aims to determine the effect of fashion trends on the TikTok application on the selection of college outfits. This study is a type of descriptive quantitative research. The population in this study were students of the Family Welfare Education study program, FKIP, Syiah Kuala University, who often use the TikTok application. The technique used in determining the sample was the Simple Random Sampling technique, so the number of samples was 73 people. Data collection in this study used a questionnaire with a Likert scale. The results showed that the simple linear regression equation had a value of